PENGARUH WAKTU SIMPAN FILM PLASTIK BIODEGRADASI DARI PATI KULIT SINGKONG TERHADAP SIFAT MEKANIKALNYA - Fauzi Akbar; Zulisma Anita; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2013)
Biodegradable plastics are plastics that will decompose in nature with the help of microorganisms. The use of starch as the main material of plastic manufacturing has great potential because in Indonesia there are different starch crops. To obtain bioplastics, starch is added to the plasticizer glycerol, in order to obtain a more flexible plastic and elastic. This study reviews the use of cassava starch and glycerol skin as a base for the manufacture of biodegradable plastics. The purpose of this research is to know the effect of storage time on the mechanical properties of plastic film biodegradation of starch cassava peel. The results obtained in the form of a thin sheet plastic film that have been tested mechanical properties such as tensile strength, elongation at break, and elasticity. Mechanical properties of plastic films will decrease every week due to the absorption of moisture and plasticizer migration occurs in a matrix of plastic films for storage.